THE “PAULO MILTON BARBOSA LANDIM” MUSEUM OF PALEONTOLOGY AND STRATIGRAPHY (UNESP RIO CLARO) AS SPACE OF INCLUSIVE EDUCATION (Editora Impacto Científico, 2025)
The "Paulo Milton Barbosa Landim" Museum of Paleontology and Stratigraphy, belonging to the Geology Department of UNESP Rio Claro, was created in 1991 with the purpose of maintaining an academic reference collection for students and professionals. From an educational point of view, it is a visitable space with didactic and cultural approaches. It receives students from elementary school to university level. Regarding inclusion, it welcomes specific groups of people such as the Open University for the Elderly, Youth and Adult Education, the Association of the Exceptional, the Municipal Center for the Blind, among others. It participates in events outside the University, such as the SDGs, Science Square, or brings its material to those who cannot visit it. The Museum maintains pages on social networks, where it publishes scientific and museological content. It develops the project "A Night at the Geology Museums" to receive students from evening classes. In this work, we will focus only on educational visits, without describing other daily activities, such as collection processes, fossil preparation, and cataloging, present in a Museum.DOI: https://doi.org/10.56238/edimpacto2025.074-003